Tripartite microbial augmentation of Bradyrhizobium diazoefficiens, Bacillus sp. MN54, and Piriformospora indica on growth, yield, and nutrient profiling of soybean (Glycine max L.) - Rafique, Munazza; Naveed, Muhammad; Mumtaz, Muhammad Zahid; Niaz, Abid; Alamri, Saud; Rehman, Sajid ur; Siddiqui, Manzer H.; Mustafa, Adnan (Frontiers in Microbiology, 2025)
IntroductionEnhancing productivity and nutrient content of soybean (Glycine max L.) is vital for sustainable agriculture. The utilization of beneficial bacterial and fungal strains has shown promising results in promoting plant growth and improving nutrient uptake. However, the effects of the individual and interactions of such microbes on soybean growth, yield, and nutrient profiling remain inadequately understood. Thus, there is a pressing need to comprehensively investigate the impact of tripartite microbial augmentation on soybean cultivation.MethodsThis field study aims to elucidate the synergistic mechanisms underlying the interactions between Bacillus sp. MN54, Bradyrhizobium diazoefficiens, and Piriformospora indica and their collective influence on soybean growth parameters, yield and nutritional quality.ResultsIn vivo compatibility tests revealed that consortium applications led to a maximum of 90% soybean germination. The field study demonstrated a significant increase in plant height (17.01%), nodules plant–1 (17.35%), pods plant–1 (12.11%), and grain yield (20.50%) due to triple inoculation over untreated control. The triple inoculation also significantly increased chlorophyll a, b, and leghemoglobin contents by 19.38, 21.01, and 14.28%, respectively, compared to control. Triple inoculation promoted crude fiber, protein, and oil content by 14.92, 8.78, and 10.52%, respectively, compared to the untreated control. The increase in nitrogen content by 7.33% in grains and 6.26% in stover and phosphorus by 11.31% in grains and 12.72% in stover was observed through triple application over untreated control.DiscussionOur findings highlight the potential of microbial inoculants as biofertilizers in sustainable soybean production. The triple inoculation with Bacillus sp. MN54, Bradyrhizobium diazoefficiens, and Piriformospora indica significantly improved soybean growth, yield, grain quality attributes, and nutrient uptake. This microbial consortium application could help to enhance agricultural productivity by boosting the nodulation in soybean and improving synergism between the microbial strains.